Pengaruh Cash Turn Over (CTO) , Firmsize, Dan Debt Equity Ratio (DER) Terhadap Current Ratio (CR) Diperusahaan Manufaktur Sektor Perdagangan, Jasa, Dan Investasi - Fahrizal Dwi Ramadhan; Mohammad Faiq Afifuddin (CV. ITTC INDONESIA, 2024)
This study aimed to determine Cash Turn Over (CTO), Firm Size, and Debt to Equity Ratio (DER) on Current Ratio (CR) on Manufacturing Companies in the Trade, Services and Investment Sector listed on the Indonesia Stock Exchange 2020-2023. This research method used multiple linear regression analysis with data processing using the tools Stata 17 program. The sampling method of this research used a purposive sampling technique. The F-test results showed that simultaneously Cash Turn Over (CTO), Firm Size, and Debt to Equity Ratio (DER) on Current Ratio (CR). The T-test results showed that partially, Debt to Equity Ratio (DER) on Current Ratio (CR).